If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -5y + -9x + 8y = 0 Reorder the terms: 4x + -9x + -5y + 8y = 0 Combine like terms: 4x + -9x = -5x -5x + -5y + 8y = 0 Combine like terms: -5y + 8y = 3y -5x + 3y = 0 Solving -5x + 3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. -5x + 3y + -3y = 0 + -3y Combine like terms: 3y + -3y = 0 -5x + 0 = 0 + -3y -5x = 0 + -3y Remove the zero: -5x = -3y Divide each side by '-5'. x = 0.6y Simplifying x = 0.6y
| 2x^2-lnx+1=0 | | 90-x^2=0 | | -x+3+12x=-4+4x+42 | | 5x-15x^3=5x(1-3x^2) | | (x+8)+4=x+(4+8) | | 3w^2-10w+8=0 | | -4(2+3n)=-56 | | 2(a+3)=5a-1 | | -4-4(2+4v)=-44 | | a-4(2a+4)=-44 | | 10a=45 | | 3(2+4x)=-42 | | 5(y^2-14y+49)=-90 | | 5x-12a=7-2x | | 2.4(m-3)+3.8=-32 | | 3x(x)+8x=9 | | 10n^2-9n=9 | | 6(y+x+2+x+4)=18 | | 3(x+1)+2(x+2)=2x+10 | | 5=(-6x-9) | | 6=-x^2+4x+2 | | 3(2-y)=2(1+3y)-7 | | -5k+1=1 | | -5x+3=2x^2-3x-1 | | 228x+88y=2250 | | U^2-3uv-70v^2=0 | | 110X+12Y=2250 | | 5y-1=2+y | | 5r+9+8r=180 | | t^2-23t+102=0 | | y^2+14y+52=78 | | x-4=-2x^2-x |